Evaluation of Milkfish (Chanos chanos) Breeding Activities at the Balai Besar Perikanan Budidaya Air Payau (BBPBAP) jepara - Maudina, Finda; Diamahesa, Wastu Ayu (Journal of Fish Health, 2023)
Cultivation of milkfish in Indonesia plays a central role in the fisheries sector, covering an expansive area of approximately 600,000 hectares and achieving a production of 621,393 tons in 2014. Milkfish-producing regions are distributed across various areas, including Sulawesi, Kalimantan, and Java, employing diverse cultivation technologies. Milkfish holds a crucial role in meeting food needs and contributing to the economic well-being of communities. Despite the predominantly traditional cultivation practices, yielding between 500 kg to 1 ton per hectare per year, there are also semi-intensive cultivation methods with yields reaching 3 tons per hectare per year. The high demand for milkfish seeds necessitates optimal water quality and strict supervision, serving as decisive factors in attaining optimal production outcomes. This research aims to acquire knowledge and skills related to milkfish breeding techniques, particularly at the Balai Besar Perikanan Budidaya Air Payau (BBPBAP) in Jepara. Data collection methods involve observation, active participation, and direct interviews. The results of this study indicate that the management of feed, broodstock maintenance, and feed management in milkfish breeding at BBPBAP Jepara are well-executed, supporting the success of milkfish breeding. The implications of this research can contribute positively to the development of milkfish cultivation techniques, focusing on milkfish breeding to achieve optimal production outcomes.